ONE MOSQUE, TWO QIBLAHS: Understanding the Difference in Qiblah Direction of the Nagari Suayan Mosque in West Sumatera, Indonesia (JOURNAL OF INDONESIAN ISLAM, 2019)
The difference in qiblah direction found among the congregation of the Nagari Suayan Mosque in Lima Puluh Kota Regency of West Sumatera began as there was an initiative to remeasure the qiblah direction by a caretaker and imam of the mosque. The difference had turned into a conflict between the Straight Qiblah congregation and the Skewed Qiblah congregation due to the lack of communication and dissemination regarding the change in qiblah direction. While in fact, facing the direction of qiblah during salat is a belief that both groups distinctly hold. This article explains the various contexts that underlie the difference and the idea of intragroup tolerance, which is the most significant finding in this study. Intragroup tolerance in practicing religion refers to the ability or willingness to tolerate differences in the rituals/practices found among varying congregations of the same religion. The research indicates that tolerating differences is part of a journey toward peace between two differing parties, and it may have implication on developing the definition of tolerance.